Impact of CSR and Environmental Sustainability Orientation on Environmental Performance of South Asian SMEs: Mediating Effect of Green HRM - Maryam; Sonia Sethi; Fayaz Ali Shah; Shahid Jan; Syed Noman Mustafa (Al-Qanṭara, 2023)
Purpose – There are plenty of studies investigating the impact of CSR and environmental sustainability orientation (ESO) on environmental performance however there have been a fewer attempts to evaluate the mediation effect of green human resource management (GHRM) amongst the CSR, ESO and environmental performance of SMEs particularly in the Southern context. In this purview, this current seeks to investigate the mediation effect of green human resource management in between the independent (CSR and ESO) and dependent variable (environmental performance). Design/methodology/approach – Data was gathered from senior management of Pakistani SMEs – Southern context through questionnaire survey. A total of 400 questionnaires were used in the data analysis. The study utilized both SPSS 25.0 and Smart PLS 3.2.8 for data analysis. Findings – The study concludes that there is a strong association between CSR, Green HRM and environmental performance. However, on the contrary, there is no significant influence of CSR on environmental performance. Consequently, the study main premises states that CSR, ESO and environmental performance significantly mediates by the green human resource management Research limitations/implications – The research only focuses on the SMEs sector particularly located in Pakistan – Southern context using the cross – sectional data. In addition to this, the current study considered only one variable i.e. green human resource management as a mediating variable. In this view, the future studies may consider large corporations as sample data and may also utilize the other mediating variables including environmental strategy and green competence as suggested by other studies. Practical Implications – The current study findings offers significant ramifications for managers, decision-makers, and business experts by helping them to understand the typology amongst the ESO, CSR, green human resource management and environmental performance. Originality/value – The current study enriches the existing literature by addressing the mediating effect of green human resource management (GHRM) in between CSR, ESO and environmental performance